BLENDED LEARNING AS AN ALTERNATIVE TO LIMITED FACE-TO-FACE LEARNING AT STMIK PRINGSEWU - Dewi, Novi Ayu Kristiana (JLCEdu (Journal of Learning and Character Education), 2021)
The purpose of this study was to analyze how the application of blended learning applied at STMIK Pringsewu as an alternative to face-to-face learning was limited and to find out the advantages and disadvantages of the application of blended learning. This research is a qualitative descriptive study that describes the existing phenomena without adding any treatment. Data collection techniques used are interviews, observation, documentation, and triangulation. The results of this study can be concluded that STMIK Pringsewu applies blended learning as an alternative to limited face-to-face learning. Which combines face-to-face and online learning with the help of media such as zoom meetings, google class, google meet, LMS, youtube, and WA groups. The learning compositions are 75/25, 50/50, or 25/75. The advantages of applying blended learning include increasing student learning independence, learning motivation, and more flexible learning. While the weakness is the disconnection of the internet connection when learning online, students rely more on the internet for opinions, and miscommunication between face-to-face and online learning schedules, but only a little occurs.